PROCEDURE OF RADIOTERAPHY WITH CLINICAL CARCINOMA TONGUE USING COBALT-60 UNIT IN ONCOLOGY RADIATION INSTALLATION HASAN SADIKIN HOSPITAL BANDUNG - Azmi Nur Azizah; Edy Susanto; Yeti Kartikasari (Poltekkes Kemenkes Semarang, 2018)
Background: Analysis of radiation exposure in patients with early, mid-irradiation, irradiation end and reason do 2 or 3 field radiotherapy irradiation in patients with carcinoma of the tongue in clinical radiation oncology installations dr Hasan Sadikin.Methods: The research is a qualitative research study approach. Data were collected by observation, documentation and in-depth interviews to specialist doctors sender and radiation oncology medical physicists, and Focus Group dicussion (FGD) with radiogrfer radiotherapy in November-December 2017. Data were analyzed using categorization and coding table OutdoorResults: The results showed that the procedure radiotherapy in patients with carcinoma of the tongue in the installation of radiation Oncology dr Hasan Sadikin came from consultation with a specialist onkolgi radiation, simulator, counting simulator results in TPS (Treatment Planning System), verification and irradiation using 2 (two) field Opposing left and right lateral or 3 (three) irradiation field, the opposing lateral and AP Supraclavikula a dose of 2 Gy per fraction as much as 33 times the irradiation with a total dose of 66 Gy.Conclusions: Analysis of the initial patient irradiation include planning radiotherapy, molding simulator, dose calculations, verification of irradiation and irradiation first, the patient carries balloon for fixation of the tongue, the patient's mid-irradiation control every 5x radiation, check the patient's general condition every day, and yet do replaning mask thermoplast on the masks that the narrowing so that patients feel claustrophobic if the mask is locked on the base plate so that it can be done irradiating the mask is not locked completely, the patient end of irradiation do the follow-up after a two week break from irradiating the last, then the patient is returned to the doctor sender then perform periodic controls to poly radiotherapy reason used 2 or 3 depending on the stage of the patient's radiation field and to prevent micrometastases to lymph nodes